2004
DOI: 10.1108/02652320410521737
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between service quality and behavioral outcomes

Abstract: This study examines the nature of relationships between service quality, background characteristics, and satisfaction and selected behavioral outcomes by using retail banking in Germany as its setting. Study results show that service quality is at the root of customer satisfaction and is linked to such behavioral outcomes as word of mouth, complaint, recommending and switching. However, different aspects of service quality and different consumer characteristics seem to be associated with different outcomes. Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
111
1
4

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(128 citation statements)
references
References 29 publications
10
111
1
4
Order By: Relevance
“…Specific attributes of ATM banking were adopted from empirical researches; Al Hawari et al (2006), Athanassopoulos (2000), Davies et al (1996), Howcroft (1991), Joseph and Stone (2003), Moutinho and Brownlie (1989), Patricio et al (2003), and Yavas et al (2004). 25 ATM banking attributes in total were adopted from empirical studies and were categorized into the five service quality dimensions of tangibles, reliability, responsiveness, assurance and empathy (Parasuraman, et al, 1988).…”
Section: Research Modelmentioning
confidence: 99%
“…Specific attributes of ATM banking were adopted from empirical researches; Al Hawari et al (2006), Athanassopoulos (2000), Davies et al (1996), Howcroft (1991), Joseph and Stone (2003), Moutinho and Brownlie (1989), Patricio et al (2003), and Yavas et al (2004). 25 ATM banking attributes in total were adopted from empirical studies and were categorized into the five service quality dimensions of tangibles, reliability, responsiveness, assurance and empathy (Parasuraman, et al, 1988).…”
Section: Research Modelmentioning
confidence: 99%
“…So customer satisfaction and service quality is the core heart of the industry of banking. In the consideration of a successful banking business rely on the strongly related impact of perception and the expectation of the customers [2,3]. Testing the market oriented customer expectations, scheming a system for service delivery that can satisfy the needs of customers and improve the level of performance is an imperative objective for banks to attain and retain the quality of being competitive [4].…”
Section: Introductionmentioning
confidence: 99%
“…By implication, positive word of mouth, reached by high service quality and customer satisfaction, can be used as powerful marketing tool. Yavas et al (2004) concluded that service quality is of key importance for customer satisfaction and the desired behavioural outcome such as word of mouth, recommending and switching. However, they qualified the statement considering that different aspects of service quality and different costumer characteristics can lead to different outcome.…”
Section: Servqual Model and Its Role In Measuring Service Quality In mentioning
confidence: 99%
“…It is often used to assess the service quality in traditional service industries like hospitality and catering (Lee and Hing, 1995) but also in other industries like consumer retail environment, accounting firms, real estate, hospitals and travel agencies. The model, based on Grönroos (1984) model of technical and functional service quality, consists of service system, behavioural service, service transactional accuracy and machine service as dimensions of service quality measurement (Yavas et al, 2004).…”
Section: Servqual Model and Its Role In Measuring Service Quality In mentioning
confidence: 99%